The Agronomy of Mauka (Mirabilis expansa (Ruíz & Pav.) Standl.) - A Review - F. Seminario, Juan; Chalampuente-Flores, Doris; Gendall, Harriet; Sørensen, Marten (Journal of Plant Genetics and Crop Research, 2019)
The Andean region is the centre of origin and domestication of at least 9 species of native root and tuber crops in addition to several species of native potatoes. Within this group, Mauka – also known as Miso or Taso ‒ (Mirabilis expansa Ruíz & Pav.) Standl. ‒ Nyctaginaceae) is one of the least well known, despite having much potential. It is cultivated at high altitudes (2300 to 3500 m a.s.l.) in Ecuador, Peru and Bolivia and is thought to be of pre-Inca origin. Mauka is characterized by its high nutritional value due to substantial levels of protein, calcium and phosphorus, as well as secondary metabolites with nutraceutical properties of varied application. It also has good potential as a forage plant. Based on ethnobotanical knowledge and scientific investigations, this review presents advances in the agronomic understanding of Mauka since its discovery five decades ago in several isolated rural Bolivian communities. The information presented covers both Andean and non-Andean countries. It includes results from journals on natural resources, botany, agronomy, and the congress minutes from botanical, agronomic and phytogenetic resources conferences. Theses on Mauka specifically and on phytogenetic resources in general were also reviewed. Books and manuals were reviewed in the libraries of the International Potato Center, INIAP-Ecuador, INIA-Peru and universities. The plant is described with emphasis on its agronomic traits and according to its propagation forms (seed or vegetative); in terms of its agroecology, phenology, growth dynamics and their indices, crop management, harvest and post-harvest processes. It is concluded that important advances in the understanding of the agronomy of Mauka have been accomplished. Furthermore, the review highlights aspects requiring further research, in order to develop improved production technologies to ensure its future use and conservation.
Keywords: Nyctaginaceae; high altitude crop; agronomy.